Peranan Iklim Organisasi dan Ciri Personaliti terhadap Prestasi Kerja - Edaham, Ismail (2009)
The purpose of this study was to investigate the level of each variables and the relationship between organizational climate, trait personality and job performance among officer in Ministry of Education. Out of 1500 questionnaires distributed, a total of 261 questionnaire were returned and 244 was valid to process. The data was analyze using Statistical Package For Social Science (SPSS) version 15. The finding show that the perception of majority respondent for job performance and trait personality was low and for organizational climate was high using mean that divided level into group;high and low. A Pearson Correlation was applied here to investigate a correlation between independent variable and dependant variable. Meanwhile Multiple Regression was used to see the statistical significant impact between three variable. The result indicate that a positive correlation between organization climate and four of his dimension but a support have not correlation with job performance. The overall organizational climate have a positive significant impact over job performance at significant level p<0.5 to a job performance as individual. Apart from that, show the correlation between trait personality and job performance. The total trait personality have positive significant impact on job performance at significant level p<0.5 to a job performance as individual. As a collective these two variable,organizational climate and trait personality have statistical significant on job performance.